2019
DOI: 10.1080/00207543.2019.1651946
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain in global supply chains and cross border trade: a critical synthesis of the state-of-the-art, challenges and opportunities

Abstract: Blockchain in supply chain management is expected to boom over the next five years. It is estimated that the global blockchain supply chain market would grow at a compound annual growth rate of 87% and increase from $45 million in 2018 to $3,314.6 million by 2023. Blockchain will improve business for all global supply chain stakeholders by providing enhanced traceability, facilitating digitisation, and securing chain-of-custody.This paper provides a synthesis of the existing challenges in global supply chain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
288
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 462 publications
(299 citation statements)
references
References 19 publications
0
288
0
11
Order By: Relevance
“…Blockchain in supply chain management is expected to grow at an annual growth rate of 87% and increase from $45 million in 2018 to $3,314.6 million by 2023 (Chang, Iakovou and Shi 2019).…”
Section: Blockchain In Agriculture and Food Supply Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…Blockchain in supply chain management is expected to grow at an annual growth rate of 87% and increase from $45 million in 2018 to $3,314.6 million by 2023 (Chang, Iakovou and Shi 2019).…”
Section: Blockchain In Agriculture and Food Supply Chainmentioning
confidence: 99%
“…There are various challenges for the wider adoption of blockchain technology, which are mentioned in related work under study and also in relevant survey and position papers (Chang, Iakovou and Shi 2019), (Galvez, Mejuto and Simal-Gandara 2018), (Hald and Kinra 2019), (Tribis, El Bouchti and Bouayad 2018), (Zhao, et al 2019), (Pearson, et al 2019). Table 2 lists potential benefits and existing barriers for the use of blockchain in agriculture and the food supply chain, as identified in Section 5 and Sections 6.1-6.5 respectively, as well as in (Chang, Iakovou and Shi 2019), (Pearson, et al 2019). A case study in the Netherlands revealed that SME lack the required size, scale or know-how needed, in order to invest in blockchain by themselves (Ge, et al 2017).…”
Section: Challenges and Open Issuesmentioning
confidence: 99%
“…Outdated means of data sharing: In current supply chain networks, data are shared between many organizations using paper-based documentation. Oftentimes, important documents, such as bills of lading, letters of credit, invoices, insurance policies, and various certificates, must travel with their associated goods around the world [22]. For example, about 200 communications were needed for Maersk, a global transport and logistics company, to complete a single shipment of frozen goods from Mombasa to Europe in 2014 [23].…”
Section: Problems With Today's Supply Chainmentioning
confidence: 99%
“…These communications created a stack of documents about 25 centimeters in height [24]. Constrained by this outdated and inefficient data sharing method, ships and airplanes are often delayed in ports when the paperwork does not match the carried goods [22].…”
Section: Problems With Today's Supply Chainmentioning
confidence: 99%
See 1 more Smart Citation